Direct Endovascular Thrombectomy or With Prior Intravenous Thrombolysis for Acute Ischemic Stroke: A Meta-Analysis - Chen, Jing; Wan, Teng-Fei; Xu, Tian-Ce; Chang, Guo-Can; Chen, Hui-Sheng; Liu, Liang (Frontiers in Neurology, 2021)
Background and purpose: It is unclear whether endovascular thrombectomy alone compared with intravenous thrombolysis combination with endovascular thrombectomy can achieve similar neurological outcomes in patients with acute large vessel occlusion stroke. We aimed to perform a systematic review and meta-analysis of randomized controlled trials to compare endovascular thrombectomy alone or intravenous thrombolysis plus endovascular thrombectomy in this population. Methods: We systematically searched PubMed, Embase, and ClinicalTrials.gov. We restricted our search to randomized clinical trials that examined the clinical outcomes of endovascular thrombectomy alone vs. intravenous thrombolysis plus endovascular thrombectomy. The Cochrane risk of bias tool was used to assess study quality. Random-effects meta-analyses were used for evaluating all outcomes. Results: Total three randomized controlled trials with 1,092 individuals enrolled were included in the meta-analysis, including 543 (49.7%) who received endovascular thrombectomy alone and 549 (50.3%) who received intravenous thrombolysis plus endovascular thrombectomy. The primary outcome of 90-day functional independence (modified Rankin scale (mRS) score ≤ 2) was 44.6% (242/543) in the endovascular thrombectomy alone group vs. 42.8% (235/549) in the alteplase with endovascular thrombectomy group (odds ratio (OR), 1.08 [95% CI, 0.85–1.38]; P = 0.0539). Among pre-specified secondary outcomes, no significant between-group differences were found in excellent outcome (mRS score ≤ 1) (OR, 1.12 [95% CI, 0.85–1.47]; P = 0.418), mortality at 90 days (OR, 0.93 [95% CI, 0.68–1.29]; P = 0.673), successful reperfusion (thrombolysis in cerebral infarction 2b-3) (OR, 0.75 [95% CI, 0.54–1.05]; P = 0.099), and symptomatic intracranial hemorrhage (OR, 0.72 [95% CI, 0.45–1.15]; P = 0.171). Conclusions: Among patients with acute ischemic stroke in the anterior circulation within 4.5 h from the onset, endovascular thrombectomy alone was non-inferior to combined intravenous thrombolysis and endovascular thrombectomy.